Legal regulation of the use of financial control tools for public administration of higher education institutions - Greben, Svitlana; Parashchenko, Liudmyla; Паращенко, Людмила Іванівна; Паращенко, Людмила (Scientific Center of Innovative Research, 2023)
The issue of financing higher education institutions plays an important role in the development of every society. The purpose of the article is to improve the legal regulation of the use of financial control tools for public administration of higher educational institutions. The main methods that were used in the research are: methods of comparative analysis, to compare normative acts of Ukraine, which regulate the use of financial control tools for public administration of higher education institutions; methods of analysis and synthesis, generalization methods and others. The article analyzes the main models of financial control over education funding: Anglo-Saxon and continental models. To evaluate the effectiveness of the funds spent by the state on the proposed mechanism of public administration of higher education institutions with financial control tools, which includes: a mechanism for evaluating the scientific activity of higher education institutions; the IT audit mechanism of the grounds for the formation of a state order for the training of students by institutions of higher education; the mechanism of financial control over the distribution of budget funds depending on the results of the scientific activity of theinstitution of higher education. A mechanism of public administration of higher education institutions with financial control tools has been developed, which includes such basic elements as: purpose, tasks, objects and subjects, main structural components. The main directions of interaction between subjects of the mechanism of public administration of higher education institutions with financial control tools have been established. Directions for establishing the relationship between normative acts of Ukraine on issues of public administration of institutions of higher education and instruments of financial control have been developed
Legal regulation of the use of financial control tools for public administration of higher education institutions
Keywords: financial control tools; financial control mechanism; institution of higher education; budget funds; distributionof budget funds; public administration